(untitled) (The Review of Diabetic Studies, 2024)
This study focuses on the ability of nurses and midwives to promote wound healing and control infection following surgical procedures. The motivation for selecting this topic stems from the need to better understand the challenges and complexities associated with post-surgical wound care, particularly in relation to the experiences of nurses, midwives, and patients in managing contaminated and high-risk wounds. The aim of this paper is to clarify the role of nurses and midwives in the care of post-surgical wounds among older adults, and to examine how they contribute to wound healing and the strategies they employ to manage and prevent infection. This includes wound assessment procedures, physiological and laboratory investigations, adherence to clinical guidelines, prevention of surgical site infections, and the provision of adequate postoperative nutrition as a critical factor in the healing process. In addition, the role of midwives is especially significant in the management of surgical wounds related to women’s health, particularly in the postoperative care of cesarean sections and other gynecological surgeries. Midwives play a key role in continuous wound monitoring, patient education regarding wound care practices, early identification of infection signs, and timely intervention in collaboration with the multidisciplinary healthcare team. This study adopted a narrative literature review methodology, with data obtained from university library databases and reputable online sources, specifically CINAHL, PubMed, and SAGE. The research question focused on post-surgical wound infections among older adults and the strategies used by nurses and midwives to manage and reduce these infections. The findings of this review indicate that nurses’ and midwives’ comprehensive knowledge of patients’ health conditions, age-related factors, the importance of nutrition in wound healing, surgical site infections, and strict adherence to clinical guidelines is essential for effective infection control. Such knowledge significantly enhances the wound healing process and improves overall patient outcomes